2022
DOI: 10.2147/jbm.s383059
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Knowledge, Attitude, Practice and Motivation Towards Blood Donation Among Albanian, Saudi and Turkish Citizens

Abstract: Background and Objectives Blood donation is a remarkably safe medical procedure. However, it is affected by attitudes, beliefs, and knowledge level. A knowledge, attitude, and practice survey was carried out in Albania, KSA (Kingdom of Saudi Arabia) and Turkey to understand and identify: (1) the factors that influence blood donation, and stop people from blood donation, (2) the behavior and approach of the people towards blood donation (3) the knowledge level among donors and non-donors, and (4) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This includes placing greater emphasis on the fact that blood donations are not associated with health risks to donors who are healthy. 35 Alreshidi and Sula 36 suggested a need for future planning, with emphasis on educational programmes and awareness campaigns by organisations, as an effective approach to dispel misconceptions and motivate potential blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…This includes placing greater emphasis on the fact that blood donations are not associated with health risks to donors who are healthy. 35 Alreshidi and Sula 36 suggested a need for future planning, with emphasis on educational programmes and awareness campaigns by organisations, as an effective approach to dispel misconceptions and motivate potential blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Os jovens constituem público-alvo para doação de sangue pela tendência de serem saudáveis, dinâmicos e com muitos anos de vida pela frente 10,11 . Entretanto, captar e fidelizar doadores é um grande desafio para os serviços de hemoterapia 4, [16][17][18][19][20][21][22][23][24][25][26] . Este estudo analisou CAPs dos estudantes de medicina frente à escassez de sangue iniciada em março de 2020 e perpetuada a partir do mês de abril do mesmo ano, devido à instauração de um cenário pandêmico pela COVID-19 [27][28][29][30][31][32] , revelando os principais pontos a serem trabalhados e divulgados, com o intuito de ajudar no desenvolvimento das próximas campanhas de doação de sangue e entender as principais barreiras e incentivos, a fim de obter um maior número de doadores.…”
Section: Discussionunclassified
“…Quanto à frequência em que se pode doar sangue, 54,9% dos não doadores e cerca de 20% dos doadores responderam de forma incorreta, da mesma forma como em um estudo que englobou os cidadãos albaneses, sauditas e turcos 23 . Com relação à quantidade de sangue doado em cada coleta, 26,4% dos não doadores e uma pequena parcela de 8,2% dos doadores responderam de forma equivocada.…”
Section: Discussionunclassified
“…As shown in Table 1, some scholars have suggested that blood donors should be aware of the incentives before donating (Chell et al, 2018). Some research has shown that monetary incentives appear to “crowd out” blood donors’ intrinsic motivations (e.g., feeling good about themselves or gaining social acceptance), thereby reducing the frequency of their blood donations (Alreshidi & Sula, 2022; Chell et al, 2018; Lacetera & Macis, 2010; Lacetera et al, 2012). Some studies have shown that monetary incentives can increase people's blood donation behavior (Ferrari et al, 1985; Iajya et al, 2013; Lacetera et al, 2012) and increase with the value of the reward (Iajya et al, 2013).…”
Section: Conceptual Developmentmentioning
confidence: 99%